The Relationship Between Quran Memorization Ability and Mathematics Learning Outcomes of 11th Grade Student at MA Putri Al-AAiziyah in the 2023/2024 Academic Year - Rahmawati, Astina Lusi; Arjudin; Tabita Wahyu Triutami; Nurul Hikmah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study examines the relationship between the ability to memorize the Qur'an and the mathematics learning outcomes of 11th-grade students at MA Putri Al-Aziziyah in the 2023/2024 academic year. Memorizing the Qur'an requires a high level of concentration, which also plays a role in enhancing brain performance. When brain cells are utilized positively and actively, brain performance improves, making students who are accustomed to memorizing the Qur'an tend to have better cognitive function. This research is a correlational study with a quantitative approach, involving 63 samples from a total of 170 students. Data was collected through oral tests and interviews and analyzed using the Pearson product-moment correlation. The results indicate that both mathematics learning outcomes and the ability to memorize the Qur'an are very good. The data shows that 57.14% of students have memorized 1-10 juz, 14.28% have memorized 11-20 juz, and 28.58% have memorized 21-30 juz. Based on the data analysis, a significance value of 0.042 < 0.05 was obtained, indicating a positive relationship between the ability to memorize the Qur'an and mathematics learning outcomes, with a correlation value of 0.257, signifying a weak relationship between the two variables.